Pendidikan Karakter Dalam Meningkatkan Kualitas Belajar Era Generasi Milenianl - Jamaludin As'ari; Nurus Sa’adah (Journal Education And Islamic Studies, 2023)
Abstract Etymologically, when traced from the origin of the word, the word character comes from the Latin "kharakterj", "kharassein", "kharax", which means to make sharp and make deep. Terminologically, character is defined as a way of thinking and behaving that is unique to each individual to live and work together, both within the family, community, nation and state. Character can be considered as the values ​​of human behavior related to God Almighty, oneself, and fellow human beings. The term character is associated and exchanged with the terms ethics, morals, and or values ​​and is related to moral strength, connoting "positive" not neutral. Learning is an interactive process of the results of the activities of educators and learning in a particular learning environment. Learning is a change in behavior or appearance with a series of activities, for example by reading, observing, listening and imitating. Generation Y, known as the Millennial generation, was born in 1980-1995. Generation Y is a generation that often applies creativity and focuses on self-development so they tend to choose jobs that are fun for them and tend to have fun. Millennials have a system of sensitivity to technology and make this generation smarter, millennials tend to have a curiosity about everything that is currently booming. They can be considered special because they have differences from previous generations. The influence of popular culture can be accepted by millennials, one of which is through films. This millennial generation is one of the generation groups that are very vulnerable to the effects of radicalism and intolerant actions amid the rapid flow of information circulating on social media and the internet. Because, a lot of information is not filtered and even becomes uncontrollable.